Risk analysis of adolescent sexual activity in college Surabaya, Indonesia: cross-sectional study - Qurniyawati, Eny; Husnina, Zida; Sari, Jayanti Dian Eka; Azzahra, Asma; Shabrina, Izzah Nur; Kartika, Prima; Gomaa Nasr, Nayla Mohamed (Intelektual Pustaka Media Utama, 2024)
Adolescence is characterized by active sexual hormones that can lead to sexual urges with the opposite sex. These urges, in turn, may trigger risky sexual behavior. College students, in a transitional period from adolescence to early adulthood, exhibit diversity in addressing sexual activity. This research aimed to analyze the risks associated with adolescent sexual activity in a college in Surabaya, Indonesia. The study utilizes a cross-sectional design with accidental sampling of active students aged 18-24 years. The total number of participants in this study was 221 people who filled out a questionnaire in the form of a Google Form, distributed through social media. The results show that, among all the factors identified, dating status has a significant relationship with PR 11.688 (95%CI 5.048-27.061) in engaging in risky sexual activities among adolescents. Reproductive health education at the university level is needed to reduce risky sexual activities among students.